PD-1 and ICOS counter-regulate tissue resident regulatory T cell development and IL-10 production during flu - McGee, Michael C.; Zhang, Tianyi; Magazine, Nicholas; Islam, Rezwanul; Carossino, Mariano; Huang, Weishan (Frontiers in Immunology, 2022)
Regulatory T cells that express the transcription factor Foxp3 (Treg cells) are a highly heterogenous population of immunoregulatory cells critical for maintaining immune homeostasis and preventing immunopathology during infections. Tissue resident Treg cells (TR-Treg) are maintained within nonlymphoid tissues and have shown to suppress proinflammatory tissue resident T cell responses and promote tissue repair. Human populations are repetitively exposed to influenza infections and lung tissue resident effector T cell responses are associated with flu-induced long-term pulmonary sequelae. The kinetics of TR-Treg cell development and molecular features of TR-Treg cells during repeated and/or long-term flu infections are unclear. Utilizing an Foxp3RFP/IL-10GFP dual reporter mouse model along with intravascular fluorescent in vivo labeling, we characterized the TR-Treg cell responses to repetitive heterosubtypic influenza infections. We found lung tissue resident Treg cells accumulated and expressed high levels of co-inhibitory and co-stimulatory receptors post primary and secondary infections. Blockade of PD-1 or ICOS signaling reveals that PD-1 and ICOS signaling pathways counter-regulate TR-Treg cell expansion and IL-10 production, during secondary influenza infection. Furthermore, the virus-specific TR-Treg cell response displayed distinct kinetics, when compared to conventional CD4+ tissue resident memory T cells, during secondary flu infections. Our results provide insight into the tissue resident Foxp3+ regulatory T cell response during repetitive flu infections, which may be applicable to other respiratory infectious diseases such as tuberculosis and COVID.